Contrastive representation of es in German and Turkish [Kontrastive darstellung von es im Deutschen und Türkischen] - (:unkn) unknown (My University, 2011)
The present article examines the most important uses of German es and its equivalents in Turkish from a contrastive point of view. Since these languages belong to different language families and Turkish does not have a single word which corresponds to German es, the study of es had to be from a functional perspective. The presentation is based on the German classification of es. As a SOV language Turkish, unlike German, does not require an explicit mention of the subject in the 3rd person singular/plural. All the information that is necessary for the identification of the subject is contained in the predicate. Furthermore, Turkish does not have subordinate clauses in the way Indo-European languages do. Subordinate clauses are rendered in Turkish mainly by participle constructions, gerundial constructions and passive sentences. The article attempts to bring out in detail which functions of Germans es are reproduced in which ways in translations into Turkish. © Copyright Erich Schmidt Verlag GmbH & Co. KG, 2011.